Results of inguino-crural herniorrhaphy: as per H. Fruchaud’s Method - Croci, Fabio; Gastambide, Carmelo; Terra, Eneas (Cirugía del Uruguay, 1984)
The authors discuss the results in the long term of the use of the method proposed by H. Fruchaud for the repair of inguino-crural hernias. 432 cases are studied (420 inguinal hernias and 12 crural hernias), in male patients, aged between 31 and 70, with intensive physical activity, operated at Central de Servicios Médicos del Banco de Seguros del Estado (State lnsurance Bank • Medical Services), in the period 1960-1978, having therefore a mínimum five-years' follow up. The overall percentage of recidivation was 4.86%.